2015
DOI: 10.1128/jvi.00708-15
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Influenza B Virus in Kuala Lumpur, Malaysia, between 1995 and 2008

Abstract: g Influenza B virus causes significant disease but remains understudied in tropical regions. We sequenced 72 influenza B viruses collected in Kuala Lumpur, Malaysia, from 1995 to 2008. The predominant circulating lineage (Victoria or Yamagata) changed every 1 to 3 years, and these shifts were associated with increased incidence of influenza B. We also found poor lineage matches with recommended influenza virus vaccine strains. While most influenza B virus lineages in Malaysia were short-lived, one circulated f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…16 However, we found that shifts in circulating influenza type were often not associated with an increased transmission. This does not negate the need to subtype influenza isolates in Malaysia; as previous studies from UMMC showed that switches in circulating influenza B lineage (Victoria or Yamagata) every 1 to 3 years led to poor lineage matches with recommended trivalent vaccine strains, 17,18 subtyping strains is an important method to monitor vaccine effectiveness. In this study, 14.1% of the influenza A strains remain untyped, while influenza B is not routinely typed apart from the In summary, we showed that while Malaysia does have yearround low-level influenza transmission as previously reported, the inconsistent and unpredictable seasonal peaks that occurred could be of concerning duration.…”
Section: Resultsmentioning
confidence: 99%
“…16 However, we found that shifts in circulating influenza type were often not associated with an increased transmission. This does not negate the need to subtype influenza isolates in Malaysia; as previous studies from UMMC showed that switches in circulating influenza B lineage (Victoria or Yamagata) every 1 to 3 years led to poor lineage matches with recommended trivalent vaccine strains, 17,18 subtyping strains is an important method to monitor vaccine effectiveness. In this study, 14.1% of the influenza A strains remain untyped, while influenza B is not routinely typed apart from the In summary, we showed that while Malaysia does have yearround low-level influenza transmission as previously reported, the inconsistent and unpredictable seasonal peaks that occurred could be of concerning duration.…”
Section: Resultsmentioning
confidence: 99%
“…It was initially expected that PB1, PB2 and HA would derive from the same clade of Yam-2, given that a previous report suggested these three gene segments would tend to co-assort during a reassortment event [ 8 ]. As such unique reassortment pattern from B/Malaysia/U2214/2013 virus was not observed in the majority of other ‘pure’ Yam-3-like or Yam-2-like viruses ( Fig 1 and S3 Fig ), this phenomenon could possibly be attributed to a random intra-lineage (or inter-clade) reassortment event within the Yamagata lineage [ 18 , 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, these groupings were not extended to other gene segments of the influenza B genome. Most whole-genome studies on influenza B viruses only described reassortment patterns of gene segments between lineages (or at the lineage level) [ 7 , 13 18 ] and have not described reassortment patterns at the clade and sub-clade levels. The evidence for segment reassortment within a lineage or clade in contributing to worldwide disease certainly warrants a more detailed and systematic approach of phylogenetic classification of all gene segments [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…These factors may affect virus survivability by lengthening the protective effect of droplets on viruses trapped on fomites or aerosols [ 26 , 58 60 ]. In particular, colder temperature has been found promoting influenza virus survival in aerosols [ 25 ], whereas higher humidity might increase the amount of virus particles that is deposited on the surface, hence encouraging contact transmission of the virus [ 57 ]. Malaysia has a tropical equatorial climate accompanied by two monsoon seasons, the Southwest Monsoon (May to September) and Northeast Monsoon (November to March).…”
Section: Discussionmentioning
confidence: 99%
“…A recent report on the evolution and epidemiology of influenza B virus in Malaysia form 1995–2008, which generally involved the children population, described the incidence and evolutionary changes of predominant circulating Victoria and Yamagata lineages over the years [ 25 ]. In view of this, we had conducted an influenza surveillance on more adult and elderly patients with respiratory infections and investigated the epidemiological and evolutionary dynamics of influenza B lineages circulating in Malaysia between 2012 and 2014 using phylogenetic methods.…”
Section: Introductionmentioning
confidence: 99%